Tuberculosis Coinfection Risk Towards People with HIV/AIDS in Care, Support, and Treatment Polyclinic Santa Maria Hospital Pekanbaru - ., Wardah; Melinda, R (KnE Life Sciences, 2019)
The tuberculosis patients infected by HIV and the person with both HIV/AIDS (PWHA) and tuberculosis are recognized as TB-HIV coinfected patient. When HIV infection spreads out, the amount and the function of CD4 lymphocytes decreased. These cells take a very important part of killing TB germs. The body immune system can no longer defend itself from the germ expansion. This research was aimed to analyze the Tuberculosis coinfection risk towards people with HIV/AIDS in CST Polyclinic Santa Maria hospital that had many criterias, such as age, sex, educational level, marital status, and employment, the factor of HIV infection risk, passed follow up medication history, and the number of CD4. This research used Case Control Analytical Descriptive design with Retrospective data during the period of January – December 2017 to the 18 respondents (total sampling). This research had been held on June 2018, in Care, Support, and Treatment polyclinic of Santa Maria Hospital Pekanbaru, and the data was proceeded with computer system. As the result of the research, the highest percentage of TB-HIV coinfection number from people with HIV/AIDS was found in the age of 36-45 years old which consisted of 8 respondents (44.4%) and in the age of 26-35 years old consisted of 6 respondents (33.3%), men who got coinfectedwere 14 respondents (77.8%), employed respondents were 16 (77.8%), the entrepreneurs were 7 respondents (38.8%), married respondents were 10 (55,6%), the infection risk were 100% because of the sexual intercourse where the heterosexual took part were 14 people (77.8%), and the CD4 amount <200 cells/mm3 were 17 people (94.4%). Keywords: risk factor, coinfection, tuberculosis, HIV/AIDS